Behavioral evaluation of auditory stream segregation in rats. (April 2019) - Noda, Takahiro; Takahashi, Hirokazu
Highlights: The behavioral expression of auditory streaming effect in rats was examined. In go/no-go task, rats detected segregated tones with larger frequency differences. No auditory streaming effect in rats in longer tone intervals in the ABA- tones. Rat is a useful animal model for probing neural mechanisms of auditory streaming. Abstract: Perceptual organization of sound sequences into separate sound sources or streams is called auditory stream segregation. Neural substrates for this process in both the spectral and temporal domains remain to be elucidated. Despite abundant knowledge about their auditory physiology, behavioral evidence for auditory streaming in rodents is still limited. We provided behavioral evidence for auditory streaming in the go/no-go discrimination task, but not in the two-alternative choice task. In the go/no-go discrimination phase, rats were able to discriminate different rhythms corresponding to segregated or integrated tone sequences in both short inter-tone interval (ITI) and long ITI conditions. Nevertheless, performance was poorer in the long ITI group. In probe testing, which assessed the ability to discriminate one of the segregated tone sequences from ABA- tone sequences, the detection rate increased with the difference in frequency (ΔF) for short (100 ms), but not long (200 ms) ITIs. Our results indicate that auditory streaming in rats on both the spectral and temporal features in the ABA- tone paradigm is qualitatively analogous to that observed in human psychophysics studies. This suggests that rodents are a valuable model for investigating the neural substrates of auditory streaming.